Comparison of Utilization of Conventional and Advanced Methods for Traffic Accidents Scene Documentation in the Czech Republic. (2017) - Stáňa, Ivo; Tokař, Stanislav; Bucsuházy, Kateřina; Bilík, Martin
Abstract: Documentation of the traffic accidents scene is one of the main assumptions and input facts for subsequent accident process analysis. This contribution points out major deficiencies (especially lower accuracy and efficiency) of currently used conventional methods (triangular method, rectangular measurement) and means (surveying wheel, steel tapeline) for the documentation of serious accidents scenes. The article presents an advanced method of localization and traffic accidents scene documentation using geodetic total station (or GNSS) and photographic documentation of traces with selected points for subsequent rectification, possibly using an image from UAV. Indisputable advantages (particularly significant time savings), significantly more accurate traffic accidents scenes documentation results for police in the Czech Republic are evident from performed comparison of these methods at the real road accidents.